2014
DOI: 10.3109/07420528.2014.937491
|View full text |Cite
|
Sign up to set email alerts
|

Association between light exposure at night and insomnia in the general elderly population: The HEIJO-KYO cohort

Abstract: Chronic circadian misalignment between the internal and environmental rhythms, which is typically related to night-shift work and clock-gene variants, is associated with disruption of suprachiasmatic nucleus function and increased risk of insomnia. Under controlled laboratory conditions, light at night (LAN) suppresses melatonin secretion, delays the internal biological rhythm, and reduces sleepiness. Therefore, LAN exposure may cause circadian misalignment and insomnia, though it remains unclear in real-life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 31 publications
0
34
3
Order By: Relevance
“…Therefore, it may be that any amount of evening sunlight exposure is detrimental to sleep. While natural and artificial light during the biological night has been found to negatively affect sleep [24,31,33,34], we found that the amount of evening light after 8 pm was not associated with poorer sleep outcomes. Thus, the timing of light exposure, which we could not assess, may be a more relevant factor and warrants further study.…”
Section: Sunlight Exposure and Sleep Outcomescontrasting
confidence: 53%
“…Therefore, it may be that any amount of evening sunlight exposure is detrimental to sleep. While natural and artificial light during the biological night has been found to negatively affect sleep [24,31,33,34], we found that the amount of evening light after 8 pm was not associated with poorer sleep outcomes. Thus, the timing of light exposure, which we could not assess, may be a more relevant factor and warrants further study.…”
Section: Sunlight Exposure and Sleep Outcomescontrasting
confidence: 53%
“…In addition, the study included a large sample of objective sleep measurements in a general elderly population. Previous studies have suggested that endogenous melatonin levels and bedroom light intensity are associated with nocturia and sleep quality [28,29]. Typically, NV with the bedroom light turned on might suppress melatonin secretion and lead to sleep disturbance.…”
Section: The Associations Between Objective and Subjective Measures Omentioning
confidence: 99%
“…The subjects were usually from 20 to 40 years old, being somewhat older than in those presented in SM 1. One study was conducted with pre-school children (Akacem et al 2016) and one with elderly (Obayashi et al 2014) adults. Light levels were typically measured for 24 h per day providing insight on the longterm light exposure profiles.…”
Section: Specific Light Exposure Affecting Melatonin Secretionmentioning
confidence: 99%